2014
DOI: 10.1186/s12884-014-0422-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy Body Mass Index (BMI) and delivery outcomes in a Canadian population

Abstract: BackgroundWorldwide there has been a dramatic increase in the prevalence of overweight and obesity in women of childbearing age. Growing evidence suggests that maternal overweight and obesity is associated with poor maternal and perinatal outcomes. This study evaluated the impact of maternal pre-pregnancy overweight and obesity on pregnancy, labour and delivery outcomes in a cohort of women with term, singleton pregnancies cared for by family physicians in community based practices.MethodsThis study is a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
70
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 35 publications
15
70
2
6
Order By: Relevance
“…12 As to hypertensive disorders of pregnancy, studies have shown that these conditions are more likely to occur in women who developed a greater GWG; however, most of these studies have significant methodological limitations, since women who developed such hypertensive comorbidities are more likely to present with edema during pregnancy than the normotensive women, and this can result in a higher GWG. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 As to hypertensive disorders of pregnancy, studies have shown that these conditions are more likely to occur in women who developed a greater GWG; however, most of these studies have significant methodological limitations, since women who developed such hypertensive comorbidities are more likely to present with edema during pregnancy than the normotensive women, and this can result in a higher GWG. 2 …”
Section: Discussionmentioning
confidence: 99%
“…12 Sobre as desordens hipertensivas na gestação, os estudos têm demonstrado que estas estão mais propensas a acontecer nas mulheres que desenvolveram maior GPG; entretanto, a maioria desses estudos tem importantes limitações metodológicas, pois as mulheres que desenvolvem tais comorbidades hipertensivas são mais propensas a apresentarem edema durante a gestação do que as normotensas, e isso, por sua vez, pode resultar em maior GPG. 2 …”
Section: Discussionunclassified
“…Accumulating evidence suggests that higher BMI prior to pregnancy is associated with an increased risk of preeclampsia, gestational diabetes, caesarean section, postpartum hemorrhage, and fetal macrosomia1234, whereas maternal underweight is associated with an increased risk of preterm delivery and small-for-gestational-age (SGA)56. Maternal GWG has also been widely studied as an independent indicator of adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…Las mujeres obesas requieren una atención prenatal y manejo del parto y el puerperio que difi eren de la gestante con peso apropiado. Así, entre otros, las mujeres obesas ti enen más riesgo de ser someti das a inducción del parto y de intervenciones obstétricas en el parto, especialmente la realización de cesáreas (45) . También la gestante obesa requiere de comodidades especiales durante el trabajo de parto y parto que no siempre se encuentran en los centros de atención de parto públicos y privados.…”
Section: Manejo De La Gestante Obesa Recomendaciones De Acogunclassified